(untitled) (Research, Society and Development, 2022)
The present work aims to study the impact of the infection by the Coronavirus on the continuity of life and on the perpetuation of the species, considering that the generation of a healthy embryo is extremely important, especially in the present scenario in which the birth rate is increasingly being reduced, it is the need for an investigation increases, as there are already several changes found in recent studies that estimate that Covid-19 may generate more serious complications and, with this, the possibility of compromising reproductive health, causing even more lack of control of the birth. Through a literature review, the interferences and possible impairment of fertility are verified in the work, considering that it was developed from reliable bases such as Nature, Pubmed and Scielo, the analysis makes it possible to perceive that many of the fertility parameters are altered after patient infected. Finally, for the study carried out, information about the factors that interfere with fertility were used, using studies applying In vitro, In vivo tests, and analysis of literature review that present research related to infection.